Marx contra o capital e o Estado: crítica radical e práxis metapolítica - Musetti, Felipe Ramos (2022)
The present thesis intent to investigate the Marxian critique of the State and politics, whose development begins in 1843, in the first settling of accounts with Hegelian philosophy, and unfolds throughout Marx’s oeuvre. It attests that, since its first theoretical formulations, the critique of politics is connected with the economic critique, considering that the State and of legal relations are rooted in civil society, whose anatomy must be searched in political economy. By following the author’s intellectual itinerary, from the formative period to the so called maturing work, the thesis seeks to highlight the continuity in Marx’s conceptions – especially regarding the recognition of politics as a negative determination –, considering that, from the 1850s onwards, economic critique is developed, apparently, separated from the critique of politics, unfolded mainly in texts dedicated to conjunctural analyses. It is argued that the mature economic critique and political analyzes developed after the 1850s complement each other as abstract and concrete moments of Marxian science, which, guided by statutory ontology, intends to apprehend the fundamental legalities of the social structure in its connections with conjunctural determinations, aiming the differentia specifica of the social reality under investigation. It is understood that the hole Marxian work supports the recognition of politics as a negative determination, produced by the alienation between individual and community. Such recognition is presented, in the Author’s mature work, in the complex unity between the economic critique and the body of political analysis texts – especially those dedicated to the French revolutions –, from which the Marxian theory of State and politics can be extracted. This theory apprehends State and politics not only in its most general forms – the State and politics as such –, but also in the concrete forms assumed by the modern State (Republic and Bonapartism). In addition, it is pointed out that Marxian theory of the State and politics achieve its final shape with the analysis of the “political form of the economic emancipation of labour”, finally discovered by the Paris Commune